Indian women novelists / editedby R.K. Dhawan.. - Dhawan, R. K. (Rajinder Kumar) (Prestige Books, 1995)
Summary, Anthology of articles on contemporary Indian women novelists writing in English, excludingthose covered in the second set; with a focus on feminism and feminist literature